Substance P scavenger enhances antioxidant defenses and prevents prothrombotic effects on the rat lung after acute exposure to oil smoke - Li-Ching Chang; Yu-Ching Lin; I-Ju Lai; Ping-Chia Li; Wen-Chung Chen (Journal of Biomedical Science, 2009)
Abstract Background Airborne particulate matter, from cooking oil, smoking, engine exhaust and other sources, is associated with the development of atherosclerosis and myocardial infarction. In order to explore the cellular and molecular events following exposure of rats to lard oil smoke, we measured the generation of reactive oxygen species (ROS), substance P, cellular adhesion molecules, and thrombosis in relation to inhibitors of substance P, the NK-1 receptor, and antioxidants. Methods Rats were exposed to oil smoke for 120 min with or without 20 min pretreatment with lovastatin (substance P scavenger), L733060 (NK-1 receptor antagonist), vitamin E (antioxidant) or catechins (antioxidant). The levels of substance P and ROS were measured. Histological studies observed ROS damage in the form of HEL adducts. The prothrombotic effects of oil smoke exposure were measured by experimental induction of thrombosis in vivo. Results Oil smoke exposure significantly increased substance P levels, ROS levels, ROS damage (HEL adduct levels), and the size of experimentally induced thrombi. The pretreatments reduced all of these effects of oil smoke exposure; at many time points the reductions were statistically significant. Conclusion We established a connection between oil smoke exposure and thrombosis which involves substance P and its receptor, the NK-1 receptor, and ROS. This study helps establish a mechanistic explanation of how airborne particulate matter can increase the risk of cardiovascular illness.